New Tests of the Life Cycle and Tax Discounting Hypotheses - Mariano, Roberto S. (Institutional Knowledge at Singapore Management University, 1985)
We first test a version of the permanent income consumption function recently suggested by Barro. The results support the theory except that consumption expenditures show sensitivity to transitory income. Next we use the consumption model to test the tax discounting hypothesis, which is strongly supported. This support for tax discounting disagrees with results from some earlier studies using more traditional specifications of the consumption function. However, we show that when certain obviously inadequate estimation procedures are corrected, the traditional models also support tax discounting. This uniform support for tax discounting suggests that the sensitivity of consumption to transitory income is not due to liquidity constraints.